Theology and science fiction - McGrath, James F. 1972- (Cascade companions, 2016)
"What is the difference between a god and a powerful alien? Can an android have a soul, or be considered a person with rights? Can we imagine biblical stories being retold in the distant future on planets far from Earth? Whether your interest is in Christianity in the future, or the Jedi in the present--and whether your interest in the Jedi is focused on real-world adherents or the fictional religion depicted on the silver screen--this book will help you explore the intersection between theology and science fiction across a range of authors and stories, topics and questions. Throughout this volume, James McGrath probes how science fiction explores theological themes, and vice versa, making the case (in conversation with some of your favorite stories, TV shows, and movies) that the answers to humanity's biggest questions are best sought by science fiction and theology together as a collaborative effort."--Resumé vydavatele